Molecular and morphological characterization of Austrodiplostomum ostrowskiae Dronen, 2009 (Digenea: Diplostomatidae), a parasite of cormorants in the Americas. Issue 2 (4th March 2015) - García-Varela, M.; Sereno-Uribe, A.L.; Pinacho-Pinacho, C.D.; Domínguez-Domínguez, O.; Pérez-Ponce de León, G.
Abstract: The diplostomid genus Austrodiplostomum currently contains two species, i.e. A. mordax and A. ostrowskiae . Adults of these species inhabit the intestine of cormorants of the genus Nannopterum, whereas larval forms (metacercariae) are found in the eyes (vitreous humor) of freshwater fishes. Records of both species have been established across a wide geographic range in the Americas. Diplostomid adults and metacercariae were collected from a wide geographical range that spans from south-eastern Mexico, southwards to Central and South America. Even though the diplostomid has been largely reported in Mexico as Diplostomum ( Austrodiplostomum ) compactum, our specimens were identified morphologically as A. ostrowskiae . Sequences of the mitochondrial gene cytochrome c oxidase ( cox 1) were obtained for 86 individuals, including 15 adults recovered from the intestine of Nannopterum brasilianus, in five localities, and 71 metacercariae from the eyes of ten fish species, in 13 localities. Sequences were used to evaluate the genetic diversity, and to test conspecificity of these specimens with the available sequence of A. ostrowskiae . Sequences were aligned with another 12 taxa representing five genera of Diplostomatidae, forming a dataset of 104 taxa with 478 nucleotides. The genetic divergence estimated among the 86 sequenced individuals, and that of A. ostrowskiae from the double-crested cormorant, Nannopterum auritus, in the USA, was very low, ranging from 0 to 0.8%. The maximum likelihood (ML) and Bayesian consensus trees showed that all sequences nested within a monophyletic lineage, with strong bootstrap and Bayesian posterior probability support values (100/1.0). In conclusion, a link between the metacercariae in fish and the adults in cormorants was established, indicating also that a single species is found in the distribution range comprising southern USA, southwards to Venezuela. Previous records of this species, particularly from Mexico, need to be corrected.